Variation in Plantar Load Distribution and Calf Muscles Activities in Legally Blind Subjects - Abdulkhudhur, Kawthar Ali; Salaam, Maryam Hassan; Raouf, Fatima Emaad Hama; Baidaa Hassan Hammoud (American Journal of Botany and Bioengineering, 2025)
Balance and locomotion in humans rely on visual, vestibular, and proprioceptive inputs, with visual impairment significantly affecting postural control. Despite existing studies on plantar pressure distribution and muscle activity, research on legally blind individuals remains limited. This study examines variations in plantar load distribution and calf muscle activity among legally blind subjects using plantar pressure sensors and electromyography (EMG). Findings indicate increased muscle activation and altered plantar pressure distribution in visually impaired individuals, suggesting a compensatory mechanism to maintain stability. Results highlight the importance of proprioceptive adaptation in mobility and emphasize the need for tailored rehabilitation programs to enhance balance and gait efficiency in visually impaired individuals.